PEDIATRIC PATIENTS AND MEDICATION USED FOR ANXIETY MANAGEMENT -a narrative review - Dana Gabriela Budală; Carmen Diana Nicoleta Savin; Eugeniu Mihalaș; Ana Elena Sîrghe; Vasilica Toma (Romanian Dental Association for Education, 2022)
Behavioral management approaches are employed with youngsters who are scared or unwilling to cooperate. Podiatric patients' discomfort and anxiety can be alleviated by the use of pharmacologic sedation, anesthesia, and analgesia. Oral sedative midazolam is frequently prescribed for children because of its safety, rapid onset, and mild amnesia, all of which make it a popular choice among pediatricians. Midazolam/ketamine and its combinations are discussed in this review article, covering the advantages of using oral route of sedation, pharmacokinetics and range of oral dosages, and the use of antagonists for clinical dentistry treatment procedures.